2005
DOI: 10.1538/expanim.54.385
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Over-expressing Dicarbonyl/L-xylulose Reductase Gene Crossed with KK-Ay Diabetic Model Mice: An Animal Model for the Metabolism of Renal Carbonyl Compounds

Abstract: Carbonyl compounds in the blood stream tend to accumulate in the kidney

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 25 publications
1
23
1
Order By: Relevance
“…13,14) To examine the relevance of DCXR in the kidney, we generated transgenic (Tg) mice for DCXR. 15) Further crossing the DCXR Tg mice with KK-A y type 2 diabetic model mice, we found that over-expression of DCXR suppressed the increase in body weight and serum glucose levels associated with a diabetes-prone genetic background in the hybrid Tg/A y mice as compared to their +/A y littermates. 15) In this study, we investigated the relevance of DCXR in the clearance of oxidative stress and subsequent fibrosis by employing an acute renal failure model, UUO, which is known to generate oxidative stress in obstructed kidneys.…”
mentioning
confidence: 82%
See 4 more Smart Citations
“…13,14) To examine the relevance of DCXR in the kidney, we generated transgenic (Tg) mice for DCXR. 15) Further crossing the DCXR Tg mice with KK-A y type 2 diabetic model mice, we found that over-expression of DCXR suppressed the increase in body weight and serum glucose levels associated with a diabetes-prone genetic background in the hybrid Tg/A y mice as compared to their +/A y littermates. 15) In this study, we investigated the relevance of DCXR in the clearance of oxidative stress and subsequent fibrosis by employing an acute renal failure model, UUO, which is known to generate oxidative stress in obstructed kidneys.…”
mentioning
confidence: 82%
“…15) Further crossing the DCXR Tg mice with KK-A y type 2 diabetic model mice, we found that over-expression of DCXR suppressed the increase in body weight and serum glucose levels associated with a diabetes-prone genetic background in the hybrid Tg/A y mice as compared to their +/A y littermates. 15) In this study, we investigated the relevance of DCXR in the clearance of oxidative stress and subsequent fibrosis by employing an acute renal failure model, UUO, which is known to generate oxidative stress in obstructed kidneys. 16,17) The accumulation of renal dicarbonyls in the UUO-operated DCXR Tg mice was measured by ESI/LC/MS, and the expression of a collagen type III gene was monitored by in situ hybridization together with an immunohistochemical examination of the DCXR protein.…”
mentioning
confidence: 82%
See 3 more Smart Citations